Failure of MIBG scan to detect metastases in SDHB‐mutated pediatric metastatic pheochromocytoma. Issue 11 (14th April 2017) - Sait, Sameer; Pandit‐Taskar, Neeta; Modak, Shakeel
Abstract: 123 I‐meta‐iodo benzyl guanidine (MIBG) scans are considered the gold standard imaging in neuroblastoma; however, flouro deoxy glucose positron emission tomography (FDG‐PET) scans have increased sensitivity in adults with pheochromocytoma/paraganglioma. We describe a pediatric patient initially considered to have localized neuroblastoma based on anatomical imaging and 123 I‐MIBG scan, but subsequent investigations revealed germline succinate dehydrogenase complex iron sulfur subunit B (SDHB) mutation–associated pheochromocytoma with multiple FDG‐avid skeletal metastases. We then compared 123 I‐MIBG and FDG‐PET scans in children with metastatic pheochromocytoma/paraganglioma. FDG‐PET was superior to 123 I‐MIBG scan for the detection of skeletal metastases (median number of skeletal lesions detected 10 [range 1–30] vs. 2 [range 1–26], respectively; P = 0.005 by t‐test). FDG‐PET should be considered the functional scan of choice in children with pheochromocytoma/paraganglioma.